Traditional Chinese Medicine Jiuwei Zhenxin Granules in Treating Depression: An Overview - Wang J; Wu X (Neuropsychiatric Disease and Treatment, 2020)
Jing Wang, Xingmao Wu Department of Critical Care Medicine, Shengjing Hospital of China Medical University, Shenyang, Liaoning, People’s Republic of ChinaCorrespondence: Xingmao WuDepartment of Critical Care Medicine, Shengjing Hospital of China Medical University, Heping District, Shenyang, Liaoning 110004, People’s Republic of ChinaTel/ Fax +86 24 18940251899Email cmu_xingmaowu@sina.comAbstract: Depression is known as “Yu Zheng” in traditional Chinese medicine (TCM). Jiuwei Zhenxin granules (JZG) is a type of TCM. According to TCM theory, it nourishes the heart and spleen, tonifies Qi, and tranquilizes the spirit, and may also has effects in the treatment of depression. Here, we systematically reviewed recent basic and clinical experimental studies of JZG and depression, including studies of the pharmacological mechanisms, active ingredients, and clinical applications of JZG in depression treatment. This review will deepen our understanding of the pharmacological mechanisms, drug interactions, and clinical applications of TCM prescriptions and provide a basis for the development of new drugs in the treatment of depression.Keywords: Jiuwei Zhenxin granules, depression, Yu Zheng, pharmacological, effective substance